2021
DOI: 10.3389/fphar.2021.573500
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine for Chemotherapy-Induced Leukopenia: A Systematic Review and Meta-Analysis of High-Quality Randomized Controlled Trials

Abstract: Aim: We conducted a systematic review of high-quality randomized controlled trials (RCTs) to assess the efficacy and safety of Chinese herbal medicine (CHM) for the treatment of chemotherapy-induced leukopenia (CIL).Methods: Eight electronic databases were searched from the date of inception to November 4, 2020 for high-quality RCTs that met the requirements of at least four key domains of the Cochrane risk of bias (RoB) tool. RevMan 5.3 was applied for the meta-analysis.Results: Fourteen RCTs involving 1,053 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Several clinical trials confirm that Chinese herbal medicine has been employed for the treatment of chemotherapy-induced leukopenia. SSD is one of the components that plays a significant role in the treatment of patients with leukopenia, which includes Husui decoction, Qijing Shengbai granules, modified Sancai Fengsui decoctions, Sanhuang Sanxian decoctions, and Bazhen decoctions [ 164 , 165 , 166 , 167 ]. An exclusive invention in the field of medicine formulation allows for the treatment of thrombocytopenia after radio–chemotherapy, using a decoction of Chinese medicinal herbs.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Several clinical trials confirm that Chinese herbal medicine has been employed for the treatment of chemotherapy-induced leukopenia. SSD is one of the components that plays a significant role in the treatment of patients with leukopenia, which includes Husui decoction, Qijing Shengbai granules, modified Sancai Fengsui decoctions, Sanhuang Sanxian decoctions, and Bazhen decoctions [ 164 , 165 , 166 , 167 ]. An exclusive invention in the field of medicine formulation allows for the treatment of thrombocytopenia after radio–chemotherapy, using a decoction of Chinese medicinal herbs.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Recently, systematic reviews and meta-analyses have suggested that various herbal treatments can be helpful for treating leukopenia or neutropenia induced by chemotherapy 5 , 6 ; however, the search and data analysis were conducted without limiting the composition of herbal medicines. Therefore, the effectiveness of specific prescriptions was not mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Many traditional Chinese medicines can be used to treat leukopenia [11,12]. Studies have shown that Chinese medicine compounds have a good effect in treating leukopenia [13].…”
Section: Introductionmentioning
confidence: 99%